Inhibiting Ceramide Synthesis Attenuates Hepatic Steatosis and Fibrosis in Rats With Non-alcoholic Fatty Liver Disease - Jiang, Meng; Li, Chun; Liu, Qiaoshu; Wang, Aimin; Lei, Minxiang (Frontiers in Endocrinology, 2019)
Nonalcoholic fatty liver disease (NAFLD) is one of the most common metabolic disorder diseases, which include a histological spectrum of conditions ranging from simple steatosis to nonalcoholic steatohepatitis (NASH). Dysregulated metabolism of sphingomyelin in the liver plays a critical role in the pathogenesis of NAFLD. Ceramides are central molecules of sphingolipid biosynthesis and catabolism and play an important role in insulin resistance, apoptosis, and inflammation. In addition, apoptosis is a main contributor to the development of NAFLD. This study detected whether the inhibition of ceramide synthesis ameliorated hepatic steatosis and fibrosis in rats with NAFLD. Sprague-Dawley rats were used to establish the NAFLD model. Here, we showed that hepatic ceramide, steatosis and fibrosis increased in liver tissue from rats with NAFLD. Chronic treatment with myriocin inhibited ceramide and lipid accumulation and improved fibrosis in liver tissue samples of high fat diet (HFD)-fed rats. In addition, hepatic inflammation and apoptosis were markedly ameliorated in HFD-fed rats treated with myriocin. Furthermore, myriocin treatment regulated the expression of pro-apoptosis and anti-apoptosis proteins by inactivating the c-Jun N-terminal kinase (JNK) signaling pathway in the liver of HFD-fed rats. Collectively, ceramide plays an important role in the pathogenesis of NASH and may represent a potential therapeutic strategy to prevent NAFLD.